Detecting the Orbital Angular Momentum of Electro-Magnetic Waves Using Virtual Rotational Antenna - Chao ZHANG (Scientific Reports, 2017)
Abstract Orbital Angular Momentum (OAM) is a typical spatial mode of an Electro-Magnetic (EM) wave. Correctly detecting the OAM mode is fundamental and of foremost importance when applying the phenomenon to wireless transmission in free space. It is found that when rotating an OAM wave, a rotational Doppler shift that is proportional to the rotation speed and the OAM mode number can be observed. This property can be used for OAM detection, i.e., different OAM modes are identified by measuring the corresponding rotational Doppler frequency shifts. In previous work, this method was implemented by mechanically rotating the OAM wave, resulting in a small frequency shift. Since the high-speed mechanical rotation is hard to manufacture in a real system, it brings limitations to the bandwidth for each OAM wave. In this paper, we report on an OAM mode detection method based on digitally rotating a virtual antenna. The transmitter and receiver are physically fixed, but the Virtual Rotational Antenna (VRA) is obtained by interpolating the signals received from transverse-mounted receiving antennas. A large rotational Doppler shift occurs as a consequence of using digital processing, resulting in more capability for wideband wireless data transmission with the larger shifted frequency.